2010
DOI: 10.1242/dev.045203
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 is a major negative regulator of cartilage vascularization, bone marrow formation and endochondral ossification

Abstract: SUMMARYSOX9 is a transcription factor of the SRY family that regulates sex determination, cartilage development and numerous other developmental events. In the foetal growth plate, Sox9 is highly expressed in chondrocytes of the proliferating and prehypertrophic zone but declines abruptly in the hypertrophic zone, suggesting that Sox9 downregulation in hypertrophic chondrocytes might be a necessary step to initiate cartilage-bone transition in the growth plate. In order to test this hypothesis, we generated tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
224
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(246 citation statements)
references
References 59 publications
21
224
0
1
Order By: Relevance
“…The discrepancy in our findings could be explained by the different cell types and treatments among these studies. Consistent with our findings indicating that Sox9 is involved in TGF-b/Cdc42-mediated chondrogenesis, transgenic mice misexpressing Sox9 in hypertrophic chondrocytes reveal the features of growth plates that are similar to those of Prx1Cre; Cdc42 fl/fl mice (Hattori et al 2010). In addition, a study of TGF-b type II receptor (Tgfbr2) knockout mice (Prx1Cre; Tgfbr2 fl/f ) also reveals that Col2-expressing cells exhibited a less-organized columnar distribution than the controls, whereas hypertrophic chondrocytes are larger but decreased in expression of Col10 characterized in both Prx1Cre; Cdc42 fl/fl and Col2Cre;Cdc42 fl/fl long bones (Spagnoli et al 2007;Aizawa et al 2012;Suzuki et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…The discrepancy in our findings could be explained by the different cell types and treatments among these studies. Consistent with our findings indicating that Sox9 is involved in TGF-b/Cdc42-mediated chondrogenesis, transgenic mice misexpressing Sox9 in hypertrophic chondrocytes reveal the features of growth plates that are similar to those of Prx1Cre; Cdc42 fl/fl mice (Hattori et al 2010). In addition, a study of TGF-b type II receptor (Tgfbr2) knockout mice (Prx1Cre; Tgfbr2 fl/f ) also reveals that Col2-expressing cells exhibited a less-organized columnar distribution than the controls, whereas hypertrophic chondrocytes are larger but decreased in expression of Col10 characterized in both Prx1Cre; Cdc42 fl/fl and Col2Cre;Cdc42 fl/fl long bones (Spagnoli et al 2007;Aizawa et al 2012;Suzuki et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…27,43,57,58,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] While cartilage tissue engineering strategies have focused on inducing and maintaining chondrogenic phenotypes, the induction and modulation of cartilage hypertrophy is critical to the progression of EC ossification in bone regeneration designs. 9,33,34,[37][38][39][40][41][42][43]72,[77][78][79][80][81][82][83][84][85] The key transcription factor involved in initial chondrogenesis is SOX9, whereas the primary hypertrophy associated factors are runtrelated transcription factor 2 (Runx2) and myocyte enhancer factor 2C (MEF2C). 33,34,41,78 In this critical maturation stage of EC ossification, chondrocytes experience a large increase in volume (*5-to 10-fold), and downstream proteins activated by Runx2 and MEF2C transcription factors begin to remodel the surrounding ECM.…”
Section: Coupling In Vivo Developmental Engineering With Native Ecm Bmentioning
confidence: 99%
“…Furthermore, SOX9 was reported to directly bind and activate cartilage-specific regulatory elements of Col2a1, resulting in its cartilage-specific gene expression (7,8). Although SOX9 is indispensable for chondrogenesis, it was also reported to work as a negative regulator of hypertrophic differentiation (9). Several studies have reported that Winglesstype murine mammary tumor virus integration site (10), bone morphogenetic protein 2 (BMP2) (11), parathyroid hormonerelated protein (PTHrP) (12), IL-1␤ (13), and Runt-related transcription factor 2 (RUNX2) (14) can regulate SOX9 expression or activity in arthritic chondrocytes or during chondrocyte differentiation.…”
mentioning
confidence: 99%